A infecção das células B por Trypanosoma cruzi resulta em ativação da Caspase-7, clivagem proteolítica da PLC1 e morte celular - Santos, Marlus Alves dos (2017)
B lymphocytes contribute to immunity in several ways, like presentation of antigen to T cells, secretion of cytokines and the unique producer immunoglobulin cell. Publications have considered B lymphocytes important for the resistance to intracellular pathogens. Trypanosoma cruzi, an intracellular parasite and etiological agent of Chagas’ disease, sabotages humoral response by depletion of B lymphocytes, resulting in increased parasitemia and susceptibility to disease. However, the role of B lymphocytes in the pathogenesis of Chagas’ disease has been overshadowed by the emphasis on T cells research. This investigation demonstrated that T. cruzi can effectively infect B lymphocytes inducing actin polymerization at the site of parasite invasion followed by a general actin depolymerization. Phospholipase C inhibition potentiates the parasitism of B lymphocytes. Moreover, T. cruzi infection induces proteolytic cleavage of Phospholipase C-gamma1 and Caspase-7 activation in B lymphocytes. Notably, B lymphocytes do not support parasite infection and undergo to cell death.